2011
DOI: 10.5539/jas.v3n4p136
|View full text |Cite
|
Sign up to set email alerts
|

Cassava/Maize Intercrop Performance and Soil Nutrient Changes with Fertilizers

Abstract: Field trials were conducted in the forest vegetation (Ibadan) and the derived savannah (Ilora) zones of south west Nigeria to assess the yield performance of cassava/maize intercrop and soil nutrient changes with sole and some combined ratios of organic-based fertilizer (OBF) and inorganic fertilizer. Sole OBF was assessed at 2.5; 5.0 and 10.0 t ha -1 while 400 kg ha -1 NPK 15-15-15 served as the sole inorganic fertilizer treatment. The combined treatments were: 2.5 t ha -1 OBF + 100 kg ha -1 NPK 15-15-15 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…But based on the research results of Agbaje and [21] in Nigeria, found that fertilizer influence on tuber yield was not significantly affected in early-planted cassava (April), but in late-planted cassava, a significant reduction in yields was observed from the application of 400 and 800 kg ha -1 of NPK fertilizer. [22] found that cassava production was statistically similar both under inorganic or organic fertilizer treatments. [23] in his research in Nigeria, found that giving dolomite at a dosage of 5 ton ha -1 and gypsum 2.5 ton ha -1 gave the highest yield of 9.5 tons of wet tuber ha -1 , compared with 2.5 ton ha -1 of gypsum alone which produces 7.2 ton of wet tuber ha -1 .…”
Section: Agronomic Developmentmentioning
confidence: 88%
“…But based on the research results of Agbaje and [21] in Nigeria, found that fertilizer influence on tuber yield was not significantly affected in early-planted cassava (April), but in late-planted cassava, a significant reduction in yields was observed from the application of 400 and 800 kg ha -1 of NPK fertilizer. [22] found that cassava production was statistically similar both under inorganic or organic fertilizer treatments. [23] in his research in Nigeria, found that giving dolomite at a dosage of 5 ton ha -1 and gypsum 2.5 ton ha -1 gave the highest yield of 9.5 tons of wet tuber ha -1 , compared with 2.5 ton ha -1 of gypsum alone which produces 7.2 ton of wet tuber ha -1 .…”
Section: Agronomic Developmentmentioning
confidence: 88%
“…A wide array of organic materials such as animal manure, green manures, legume cover crops, and crop residues have been in use over the years and have been found to enhance crop yields and nutritional values compared to synthetic fertilizers (Ogbonna et al, 2012). However, organic manures from both plant and animal sources are not without shortcomings as they are not always readily available, and may require the extra cost and labour while acquiring them and are often needed in enormous quantities to produce noticeable effects (Adeoye et al, 2008;Ayoola, 2011). A better approach to soil fertility management consists of using balanced proportions of organic and inorganic fertilizers (Nziguheba et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…This perennial problem contributes immensely to factors that militate against food production. In fact, many reports have associated drastic decreases in maize yields with depleted soil nutrients (Ayoola, 2011;Zafar et al, 2011). The use of inorganic fertilizers has thus become a common practice as these agrochemicals help in improving soil fertility considerably.…”
Section: Introductionmentioning
confidence: 99%
“…The nutrients contained in organic manures are released more slowly and stored for a longer time in the soil, thereby ensuring a long‐term residual effect (Cai et al., 2011; Ding et al., 2011; Rahman et al., 2013; Zhang et al., 2013). Complementary use of organic manure and mineral fertilizers has proven to be a sound method in soil fertility management in many countries (Ayoola et al., 2007; Kaur et al., 2008; Xu et al., 2008; Zhou et al., 2002). Consequently, the use of organic manure in conjunction with or as an alternative to mineral fertilizer is receiving considerable attention (Hu et al., 2007; Liu et al., 2018; Saleque et al., 2004; Singh & Gangwar, 2000; Solaiman & Rabbani, 2006).…”
Section: Introductionmentioning
confidence: 99%